2003
DOI: 10.1029/2003ja009955
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of coupling between the E and F regions during unstable sporadic‐E conditions

Abstract: [1] Simultaneous F-region airglow, E-region coherent-scatter radar, and ionosonde observations were made in Greece during the summer sporadic-E season in 2002. In this paper we report on two case studies during which patchy sporadic-E layers were accompanied by midlatitude spread F, coherent VHF radar echoes (including two-stream echoes), and traveling ionospheric disturbances registered by the airglow instrument. We argue that these events give strong evidence that polarization electric fields are built up in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…Each image has been standardized so that north is at the top and east is to the right (after Kelley et al, 2002, reproduced with permission of Elsevier). Haldoupis et al (2003) and Kelley et al (2003) showed experimentally that the E-and F-regions are closely coupled in this process. Theoretical work has lagged far behind experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Each image has been standardized so that north is at the top and east is to the right (after Kelley et al, 2002, reproduced with permission of Elsevier). Haldoupis et al (2003) and Kelley et al (2003) showed experimentally that the E-and F-regions are closely coupled in this process. Theoretical work has lagged far behind experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the papers by Kelley et al (2003) and Haldoupis et al (2003), an eastward polarization electric field of 5 mV/m inside a medium-scale E s patch will map instantly up along the field lines to produce a 50-km uplift of the F region bottomside in about 10 min, whereas a 10-mV/m field will need only about 5 min for the same uplift. This process will be much more effective if both the sporadic-E patch below and the uplifted plasma region above are somehow kept "in contact", by moving horizontally with comparable velocities.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…On the other hand, Swartz et al (2002) estimated the F to E region conductance ratio to be near 5 or greater during normal conditions but drops to almost 1.5 during times when a strongly uplifted F layer above and an intense sporadic-E layer below occurred concurrently. Also, in the two spread-F events studied by Kelley et al (2003), the ratio of F to E-layer height integrated Pedersen conductivities was estimated to be in the range from 1.5 to 10. Given all this, we take 1<Z<10.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations